IMPLEMENTASI PERATURAN DAERAH NOMOR 17 TAHUN 2012 TENTANG TATA CARA PEMUNGUTAN RETRIBUSI DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PADA UPTD PASAR KENTEN AZHAR DI DINAS PERDAGANGAN, KOPERASI DAN USAHA KECIL MENENGAH KABUPATEN BANYUASIN - Reni Juliati (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Research Objectives to determine the implementation of the process of levying services market fees Azhar in Banyuasin regency and to find out the barriers that occur in an effort to increase the original income of Banyuasin regency. Metoede The research used is Qualitative Methods, Data or information collected through interviews to informants. Data Analysis Techniques used in this study using data collection, reduction, data presentation and conclusion. The result of the research shows that the Process of Retribution Levy of Market Service in Increasing Local Original Income has not been effective. This is seen from the unconsciousness of traders in the obligation of retribution and the presence of traders who do not pay the levy in accordance with the tariff that is implemented by the Government of Banyuasin. In addition, the officer's affirmation was not enough to make them pay the tariff they wanted. Keywords : Retribution, Local Original Income